The decline in marriage among African Americans : causes, consequences, and policy implications - Tucker, M. Belinda; Mitchell-Kernan, Claudia (Russell Sage Foundation, 1995)
The original, often controversial, research presented in this book links marital decline to a pivotal drop in the pool of marriageable black males. Increased joblessness has robbed many black men of their economic viability, rendering them not only less desirable as mates, but also less inclined to take on the responsibility of marriage. Higher death rates resulting from disease, poor health care, and violent crime, as well as evergrowing incarceration rates, have further depleted the male population. In documenting their observations, editors M. Belinda Tucker and Claudia Mitchell-Kernan and the contributors take a hard look at the effects of chronic economic instability on cultural attitudes toward the male role as family provider. Their cogent historical analyses suggest that the influence of external circumstances over marriage preferences stems in large part from the profoundly damaging experience of slavery.